Analysis of Economic Efficiency of Energy Wood Plantations - Csipkés, Margit (Acta Agraria Debreceniensis, 2009)
After the EU-accession we should have a definite idea about what kind of production structure and land use should Hungary obtain to meet the conditions undertaken in the different governmental decisions. In the course of Hungarian land use, significant changes have taken place in the last eighty years. Further changes are influenced by the fact that according to various decisions, legislative provisions and ideas in a short time the energy orchards’ domiciliation could start in large. For this, financial support can be required from EU-sources. As for the woody energy plants, subsidies can be required for the domiciliation and as for herbaceous plants grants can be required for growing. As far as the latter is concerned, the subsidy will be around 26-27 thousand Ft/hectares according to the plans. However, the cultivation method does not have to be changed to switch from plow-land to energy plants. The question is if the produced commodity will be received by power plants and if it ensures appropriate income for the farmer. In my research I wanted to find from the given woody energy plants which are those that are the most profitable.